The Effect of Financial Liberalization through the General Agreement on Trade and Services on Economic Growth in Developing Countries - Al Samman, Hazem; Azmeh, Chadi (International Journal of Economics and Financial Issues, 2016)
This study investigates the influence of financial liberalization on economic growth in developing countries indirectly through their effect on financial development. It selects the size and activity of the financial system as indicators of financial development. The General agreement on Trade and Services (GATS) is a very useful option for developing countries to consolidate their financial sector reform to give foreign investors more certainty about financial investment opportunities in the economies of developing countries. This study chooses the level of commitments taking by developing countries in the GATS in banking sector as a measure of financial liberalization. The main objective is to examine the effect of developing countries financial liberalization commitments at the GATS on economic growth through their effect on the size and activity of the financial sector. According to the analysis conducted, the results show no real effect of the level of commitments taking by developing countries in the GATS on Economic Growth through their effect on the size and activity of financial development. Even though the effect of financial development on economic growth is positive, the effect of financial liberalization through the GATS on financial development is almost zero. Keywords: Financial Liberalization, Economic Growth, Developing Countries, GATS, Financial Development. JEL Classifications: F65, O16